The Most Social Games: Predictors of Social Media Uses During the 2016 Rio Olympics. (June 2018) - Tang, Tang; Cooper, Roger
Social media has substantially changed how people consume media content, particularly during sport mega-events. This study examined the audience social media uses during the "most social Olympics" and found that demographics, personality, motivations, preference, media use routine, and viewing context significantly predicted social media consumption for the Rio Games. Olympics viewing on social media was predominately predicted by media use routine, while following and posting on social media about the Olympics appeared to be a more "active" choice that was shaped by personal identity and virtual schemas. In addition, results indicate that social media uses during the Rio Games neither "displaced" nor "encouraged" Olympics viewing on traditional television. Uses of social media suggest a digital expansion of "group" viewing and transform ways in which the audience can experience a sport mega-event.